FESTIVAL ANAK SHOLEH AS A STRATEGY FOR IMPROVING THE QUALITY OF CHARACTER EDUCATION IN ELEMENTARY SCHOOLS AND MADRASAS - Muhammad Yusup; Fitri Nasution; Zilawati; Yeri Anggara Dirta; Yuneni Agustin; Puji Astuti; Nazarwita; Aviq Nazifa; Kustina Simamora (International Journal of Multidisciplinary Reseach, 2026)
Character education is a central objective of Indonesian national education, particularly in strengthening students’ religious values. This study analyzes the implementation of the “Festival Anak Sholeh” as a strategic approach to improving the quality of character education in elementary schools and madrasahs. The research employed a qualitative descriptive design through community-based educational activities held at Baituttaqwa Mosque. Participants consisted of 40 children from early childhood education and elementary levels. Data were collected through participatory observation, documentation, informal interviews, and team reflection, and analyzed using the interactive model of Miles, Huberman, and Saldaña. Findings indicate that competitive-educative activities such as adhan competitions, daily prayer memorization, and mosque coloring effectively enhanced students’ religious participation, self-confidence, and internalization of Islamic values. The mosque functioned not only as a place of worship but also as a community-based character education center. The study concludes that Festival Anak Sholeh represents a replicable model for strengthening character education quality in elementary schools and madrasahs through experiential and participatory strategies.